Prevalence and factors associated with diabetic retinopathy among type 2 diabetic patients in Bangladesh: a hospital based cross-sectional study - Wahiduzzaman, Mohammad; Islam, M. Sahidul; Hossain, Sharmin; Hussain, Qazi Muhammad Iqbal; Banning, Friederike; Lechner, Andreas (International Journal Of Community Medicine And Public Health, 2022)
Background: Diabetes mellitus is a major health problem in Southeast Asia and diabetic retinopathy is one of its most debilitating complications. Nevertheless, fundoscopy and systematic evaluation of non-adherence to drug therapy are not regularly done in individuals with diabetes in Bangladesh due to limited resources. Therefore, the prevalence of diabetic retinopathy and its determinants with non-adherence to drug therapy are not known. We, therefore, screened for diabetic retinopathy, non-adherence to drug therapy and other associated factors at a tertiary care hospital in Bangladesh. Methods: Between May 2017 to September 2017, we conducted a cross-sectional study of 489 systematically recruited asymptomatic, at least one-year type-2 diabetic individuals on medication and attending the outpatient department of the BIHS tertiary care centre in Dhaka, Bangladesh. We obtained a medical history, physical examination, routine laboratory tests, questionnaires, and fundus photography. Results: The prevalence of diabetic retinopathy among T2DM patients was 18.8%. Clinical factors associated with the presence of diabetic retinopathy were uncontrolled fasting blood glucose, known duration of diabetes of ≥10 years and self-reported non-adherence to drug therapy. With a known duration of diabetes of 15 years or more, the prevalence of diabetic retinopathy rose to 40%. Conclusions: Undiagnosed diabetic retinopathy is still common among patients in Bangladesh, even at tertiary care centres. It is associated with longer disease duration, poor metabolic control and self-reported non-adherence to therapy. Regular screening for diabetic retinopathy should therefore be implemented also in resource-limited settings and further efforts should be made to improve the patients’ drug adherence and metabolic control.